2018
DOI: 10.1038/s41598-018-34032-3
|View full text |Cite
|
Sign up to set email alerts
|

Distinct amyloid distribution patterns in amyloid positive subcortical vascular cognitive impairment

Abstract: Amyloid-β (Aβ) and cerebral small vessel disease (CSVD) commonly coexist. They can occur independently by chance, or may interact with each other. We aimed to determine whether the distribution of Aβ in subcortical vascular cognitive impairments (SVCI) patients can be classified by the underlying pathobiologies. A total of 45 11C-Pittsburgh compound B PET positive (PiB(+)) SVCI patients were included in this study. They were classified using a new cluster analysis method which adopted the Louvain method, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Since our common target regions included parts of the occipital region, we calculated rdcCL in the occipital region. This has some clinical implication because cerebrovascular disease might be related to increased Aβ uptake in the occipital region [22,23]. However, the method developed in the present study provides regional as well as global rdcCL scales in the six regions including the striatum.…”
Section: Discussionmentioning
confidence: 97%
“…Since our common target regions included parts of the occipital region, we calculated rdcCL in the occipital region. This has some clinical implication because cerebrovascular disease might be related to increased Aβ uptake in the occipital region [22,23]. However, the method developed in the present study provides regional as well as global rdcCL scales in the six regions including the striatum.…”
Section: Discussionmentioning
confidence: 97%
“…Another study using clustering analyses classified SVCI patients and AD patients into the Aβ occipital-predominant and Aβ occipital-sparing groups. The frequency of the occipital-predominant group has been shown to be higher in SVCI patients (62.2%) than in AD patients (37.8%) [ 33 ]. Furthermore, the Aβ spreading pattern in patients with SVCI is quite different from in patients with ADCI.…”
Section: Imaging Markers Of Alzheimer’s Disease (Ad) and Cerebral Sma...mentioning
confidence: 99%
“…Specifically, the Aβ spreading pattern of patients with SVCI demonstrates that Aβ accumulates in the occipital area before the temporal and frontal regions, whereas in patients with ADCI, the parietal and fronto-temporal regions precede the occipital region. ( Figure 1 a) [ 33 , 54 , 55 , 56 , 57 ]. The predominant Aβ deposition in the occipital region, mainly observed in patients with SVCI, may be related to the distribution pattern of CAA or ischemic vulnerability of the posterior circulation [ 53 ].…”
Section: Imaging Markers Of Alzheimer’s Disease (Ad) and Cerebral Sma...mentioning
confidence: 99%
See 1 more Smart Citation
“…The aberrant deposition of Aβ in ADCI is related to the decreased Aβ clearance; specifically, decreased Aβ clearance can result from impaired microglial function, enzymatic degradation, perivascular Aβ drainage, and the blood–brain barrier (BBB) function ( Grimmer et al, 2012 ; Tarasoff-Conway et al, 2015 ). We previously revealed that patients with SVCI showed predominant Aβ deposition in the occipital lobe ( Jang et al, 2018 ) and WMHs were associated with Aβ deposition, particularly in posterior brain regions ( Noh et al, 2014 ). Considering that the posterior regions are vulnerable to ischemic injury, the CSVD burden may impaired Aβ clearance by creating a deficiency in perivascular Aβ drainage and in the BBB ( Grinberg and Thal, 2010 ; Zlokovic, 2011 ).…”
Section: Introductionmentioning
confidence: 99%